Characteristics of the source material for breeding winter wheat for group resistance to leaf and stem pathogens - Є. А. Голуб; Н. І. Сауляк; О. А. Васильєв; М. А. Литвиненко; В. А. Трасковецька; З. В. Щербина; М. А. Бушулян; Є. І. Кірчук (Plant Varieties Studying and Protection)
Purpose. Investigation of the efficiency of using introgressive lines with group resistance to leaf pathogens as source material in breeding winter wheat (Triticum aestivum L.) for the aforementioned trait. Methods. Field and laboratory (evaluation of resistance to certain races of leaf rust and powdery mildew at the juvenile growth stage in greenhouses and on light plants); PCR analysis (identification of resistance genes to these diseases in the studied material); statistical analysis; and crossbreeding analysis (study of patterns of inheritance and interaction of resistance genes). Results. The original breeding lines of different generations (F4–F5), which were created based on the genetics of wild wheat relatives: Aegilops cylindrica, Ae. variabilis, Triticum ventricosum, Tr. erebuni, Tr. Tauschi, Thinopyrum elongatum, Triticosecale in the PBGI – NCSCI, were studied for group resistance to local populations of leaf diseases and a set of basic agronomic traits. Six lines with effective group resistance genes (Lr24, Lr68, Sr15, Sr31, Sr58, Pm38), as well as their combinations, were identified. These lines provide the selected genotypes with a consistently high level of resistance, excellent grain quality and productivity, regardless of the severity of the infection load. Investigating the genetic basis of the group resistance trait on F1–F2 hybrid material, obtained by crossing the studied lines with susceptible local varieties, revealed that its inheritance is determined by the action of two dominant complementary genes. This indicates the possibility of effectively using this material as donors of high resistance. Conclusions. As a result of the research, we obtained source material in the form of six lines of winter bread wheat that effectively combine a high level of group resistance to leaf pathogens and a set of basic agronomic traits in their genotype. This makes them valuable breeding material. These lines are included as parental components in the crossbreeding plans of the PBGI – NCSCI and are transferred to leading NAAS of Ukraine scientific breeding centres for use in breeding programmes.